PERENCANAAN SDM STRATEGIK: MENGANTISIPASI PERUBAHAN LINGKUNGAN BISNIS YANG DINAMIS GUNA MENCAPAI COMPETITIVE ADVANTAGE - Fauzi, Agus - (Universitas Slamet Riyadi, 2005)
Abstract This article discusses human resource planning issues as strategy to response dynamic and competitive business environment changes to gain sustainable competitive advantage. Also this article discusses how the stages and human resource planning process in short term, intermediate term and long term, and discusses about how long the linkage between humen resource and strategic business planning are administrative linkage, one-way linkage, two-way linkage, and integrative linkage. The last section in this article discusses the importance gaining competitive advantage sources and human resource concentration related with business issues as the action to integrate human resource fuction in the strategic business. Keywords: Strategic human resource planning, dynamic environment change, strategic business, human resource fuction, and competitive advantage.